Selected tree methanolic extracts attenuate hyperglycemia in alloxan-induced zebrafish (Danio rerio). - Pazon, Mae Anne Sailyn (Mae Anne Sailyn Pazon, 2018)
There has been an increasing trend of exploring medicinal plants in treating ailments, such as diabetes, because of their natural origin and less side effects. In this study, the potential antidiabetic effect of the selected tree crude extracts namely Cresecentia cujete, Nauclea orientalis, Sandoricum koetjape, were investigated using zebrafish, Danio rerio, as the model organism. The adult wild-type zebrafish were divided into 4 groups: normal, control group, and hyperglycemic zebrafish treated with metformin and plant extracts (1 ug/g body). A 55% increase from the normal group's blood glucose level (BGL < 70 mg dL-) was presented after alloxan induction (BGL > 100 mg dL-). The 20% DGBL by metformin compared to the 28% increase at 90 min in control group showed its effectiveness in ameliorating hyperglycemia. All the plant extracts screened for their antidiabetic effect exhibited a significant reductions (p < 0.05) in their hyperglycemic state having 25% and 66%, 12%, and 61%, and 8% and 58% at 90 min and 180 min of C. cujete group of the hyperglycemic zebrafish at 180 min was decreased more than 3.2 times compared with the control group. Moreover, C. cujete presented a 5% higher in the % DGBL at 90 min compared to the commercial antidiabetic drug, metformin. All the screened plants tested positive for the presence of flavonoids and phenolic compounds that might provide the antidiabetic activity by enhancing insulin secretion regeneration via pancreatic B-cells. These results show that the plants screened have the potential antidiabetic properties that can attenuate hyperglycemia.